«ТАС»ҚА БАЙЛАНЫСЛЫ ИСЕНИМЛЕР - Палымбетов, К.С. (SCIENCE and SOCIETY, 2023)
The article deals with magic stones as a cult, superstition of calling wind or rain by means of stones, and also talks about their artistic function in the plots of folk epics. And also an attempt is made from a scientific point of view to analyze the meaning of the «magic stone of the cloud», «blue stone» in the plots of the Karakalpak folk epics «Koblan», «Bozuglan», «Sharyar», and it is also noted that magic stones have supernatural power in predestination and development of the subsequent fate of the heroes of epics.
Keywords: epic; superstition; tradition; cult; myth; magic stone; blue stone; cloud